Exploring the Use of Mobile Health to Improve Community-Based Health and Nutrition Service Utilization in the Hills of Nepal: Qualitative Study - Acharya, Ajay; Cunningham, Kenda; Manandhar, Shraddha; Shrestha, Niva; Chen, Mario; Weissman, Amy (JMIR Publications, 2020)
BackgroundWith mobile phone coverage and ownership expanding globally, mobile health (mHealth) interventions are increasingly being used to improve coverage and quality of health and nutrition services. However, evidence on mHealth intervention feasibility and factors to consider during program design is limited in low- and middle-income countries like Nepal. ObjectiveThis study aimed to examine the potential of using text messages to improve health and nutrition services by exploring mobile phone ownership and sharing; mobile phone use and skills; and interest, preferences, and limitations regarding mHealth interventions. MethodsWe conducted 35 in-depth interviews with 1000-day women (the period from conception to a child's second birthday), health facility staff, and female community health volunteers (FCHVs), as well as eight focus group discussions with health facility staff, FCHVs, and 1000-day household decision-makers (ie, husbands, mothers-in-law, and fathers-in-law). We also conducted a mobile phone skills test. We employed thematic analysis using framework matrices and analytical memos. ResultsThe study included 70 study participants, of whom 68 (97%) had a mobile phone, and phone sharing was uncommon. Use of text messages was most commonly reported by 1000-day women and health facility staff than household decision-makers and FCHVs. More than 8 in 10 participants (54/64, 84%) could dial numbers, and the majority (28/34, 82%) of 1000-day women, health facility staff, and male decision-makers could also read and write text messages. We found that 1000-day women preferred educational and reminder messages, whereas health facility staff and FCHVs desired educational and motivational messages. Participants suggested different types of texts for 1000-day women, families, FCHVs, and health facility staff, and reported less value for texts received from unknown phone numbers. ConclusionsA text message-based mHealth intervention is acceptable in the hills of Nepal and has the potential to improve community health and nutrition service utilization, particularly by sending meeting reminders and by providing information. Our findings contribute to text message-based mHealth intervention design in under-resourced settings.